Factors associated with knowledge and awareness of stroke in the Iraqi population: a cross-sectional study - Al-Obaidi, Hala; Khidhair, Zainab; Jirjees, Feras; Barakat, Muna; AlSalamat, Husam; Kharaba, Zelal; Alfoteih, Yassen; Haddad, Chadia; Mansour, Sara; Hallit, Souheil; Malaeb, Diana; Hosseini, Hassan (Frontiers in Neurology, 2023)
Introduction Stroke is a highly prevalent condition with high rates of death and disability in Iraq and around the world. Knowledge of stroke and its associated risk factors is essential for disease prevention and rapid response when confronted with a stroke patient. Purpose The purpose of this study is to assess stroke knowledge and identify factors associated with awareness among the Iraqi public. Material and methods A questionnaire-based, cross-sectional survey was conducted on the Iraqi population. The self-administered online questionnaire contained three sections. The study got ethical approval from the Research Ethics Committee at the University of Baghdad. Results The results showed that 26.8% of the participants reported knowledge regarding identifying all risk factors. In addition, 18.4% and 34.8% of the participants recognized all symptoms and mentioned all possible consequences of stroke, respectively. Previous medical history with chronic diseases had essential relationships with the response when faced with a person having an acute stroke. In addition, there was a significant relationship between gender, smoking history, and identification of early stroke symptoms. Conclusion There was a lack of knowledge about risk factors for stroke among the participants. There is a need for an awareness program among the Iraqi people to raise their understanding of stroke that can reduce stroke mortality and morbidity.